2015
DOI: 10.1063/1.4931079
|View full text |Cite
|
Sign up to set email alerts
|

Study of magnetic fields and current in the Z pinch at stagnation

Abstract: Magnetic field measurements via visible spectroscopy on the Z machine Review of Scientific Instruments 85, 11E609 (2014);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…We note that previous measurements in classical Zpinches have indicated that during the stagnation some of the current is carried by an imploding trailing plasma [25,31]. However, here we show a completely different phenomenon that is directly related to the presence of an applied B z .…”
supporting
confidence: 49%
See 1 more Smart Citation
“…We note that previous measurements in classical Zpinches have indicated that during the stagnation some of the current is carried by an imploding trailing plasma [25,31]. However, here we show a completely different phenomenon that is directly related to the presence of an applied B z .…”
supporting
confidence: 49%
“…However, reliable experimental data on the B-field distribution in Z-pinches are scarce due to the high electron densities, high ion velocities, and transient nature of the plasma, which make measurements of B-fields in such plasmas rather difficult. We note a few examples of such spectroscopic measurements in gas-puff Z-pinches [22][23][24], and measurements based on Faraday rotation in wire-array Z-pinches [25].…”
mentioning
confidence: 99%
“…Specifically, we measure that during stagnation the current transitions out of the SP and into a low density plasma (LDP), residing at much larger radii, while the SP continues to implode. This phenomenon might be connected to the previous observations of low current in the SP of Zpinches [11,20,[24][25][26], and might be common to various pulsed-power systems, including those of lower density plasmas [11], such as plasma switches [12][13][14] and high power transmission lines [15,16].…”
Section: Introduction -supporting
confidence: 66%
“…Note that applying the same analysis for locations farther away from the cathode, a gradually changing behavior is found: at distances of 3 mm and 5 mm from the cathode, the discharge current is never observed to flow at small radii [30], consistent with the absence of significant current in the stagnating plasma seen in previous experiments [11,20,[24][25][26].…”
Section: Introduction -supporting
confidence: 56%
See 1 more Smart Citation